Comics and the world wars : a cultural record - Chapman, Jane (Palgrave studies in the history of media, 2015)
Introduction -- A proposed theory and method for the incorporation of comic books as primary sources -- Haselden as pioneer: reflecting or constructing home front opinion? -- Proto comics as trench record: anti-heroism, disparagement humour and citizens' journalism -- The rise and fall of the World War One gullible worker as a counter culture -- Adjusting to total war: US propaganda, commerce and audience -- The cultural construction of women: pin-ups, proactive women and representation in combat -- Collective culture as dynamic record: the Daily Worker 1940-43 -- Conclusion